2007
DOI: 10.1007/s10531-007-9221-3
|View full text |Cite
|
Sign up to set email alerts
|

Testate amoebae analysis in ecological and paleoecological studies of wetlands: past, present and future

Abstract: Testate amoebae are an abundant and diverse polyphyletic group of shelled protozoa living in aquatic to moist habitats ranging from estuaries to lakes, rivers, wetlands, soils, litter, and moss habitats. Owing to the preservation of shells in sediments, testate amoebae are useful proxy indicators complementary to long-established indicators such as pollen and spores or macrofossils. Their primary use to date has been for inferring past moisture conditions and climate in ombrotrophic peatlands and, to a lesser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
235
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(246 citation statements)
references
References 116 publications
(116 reference statements)
9
235
0
2
Order By: Relevance
“…Testate amoebae, a group of amoeboid protozoans that produce morphologically distinct shells, are commonly used as surfacemoisture proxies in peat-based palaeoclimate studies (Mitchell et al, 2008a). Although the moisture sensitivity of these organisms has been recognised for over a century (Leidy, 1879;Jung, 1936), work over the past several decades has demonstrated the utility of testate amoebae as quantitative surface-moisture indicators.…”
Section: Use Of Testate Amoebaementioning
confidence: 99%
See 1 more Smart Citation
“…Testate amoebae, a group of amoeboid protozoans that produce morphologically distinct shells, are commonly used as surfacemoisture proxies in peat-based palaeoclimate studies (Mitchell et al, 2008a). Although the moisture sensitivity of these organisms has been recognised for over a century (Leidy, 1879;Jung, 1936), work over the past several decades has demonstrated the utility of testate amoebae as quantitative surface-moisture indicators.…”
Section: Use Of Testate Amoebaementioning
confidence: 99%
“…High sensitivity to moisture variation has been demonstrated by coherence in reconstructions of wet and dry fluctuations within and between mires (Hendon et al, 2001;Booth et al, 2006). Advantages of using testate amoebae in peat-based palaeoclimate studies include their rapid response time to environmental changes, the ease with which community composition can be quantified using standard light microscopy, the small sample volumes needed for analysis (i.e., 0.5e1 cm 3 ), and the ability to reconstruct past water-table depths quantitatively, including associated error estimates Charman, 2001;Mitchell et al, 2008a). A protocol is provided by Charman et al (2000) and by .…”
Section: Use Of Testate Amoebaementioning
confidence: 99%
“…changes (Charman, 2001;Mitchell et al, 2008). However, their taxonomy is still far from being resolved in a satisfactory way, and recent studies have revealed a high diversity within individual morphospecies, sometimes referred to as cryptic or pseudocryptic (Kosakyan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1). Indeed testate amoeba density and community structure were previously shown to respond to soil moisture fluctuations [25,29,[46][47][48].…”
Section: Testate Amoeba Community Composition Species Richness and Dmentioning
confidence: 99%
“…Testate amoebae are used as indicators in a variety of research fields (ecology, paleoecology, limnology, paleolimnology, paleoclimatology, peatland regeneration, soil and air pollution monitoring and ecotoxicology) because they respond to biotic and abiotic factors by abundance, community composition or even shell morphology [25,26]. Despite the strong potential of testate amoebae and other soil protozoa as bioindicators in agroecosystem and natural ecosystems (e.g.…”
Section: Introductionmentioning
confidence: 99%